2018
DOI: 10.1097/aln.0000000000002185
|View full text |Cite
|
Sign up to set email alerts
|

Early-phase Innate Immune Suppression in Murine Severe Sepsis Is Restored with Systemic Interferon-β

Abstract: A NNUALLY, 750,000 cases of sepsis are reported in the United States, 1,2 and this disease is associated with a sustained high mortality rate, ranging from 15 to 50%. 3-9 Death relates to multiple organ dysfunction that involves kidneys, liver, pancreas, adrenals, coagulation system, central nervous system, cardiovascular system, and lungs. 10 Acute respiratory distress syndrome is a major remote organ pathology accompanied by sepsis. 11 Despite an increase in our knowledge of the pathogenesis of sepsis, all s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 42 publications
0
13
0
Order By: Relevance
“…[17][18][19][20][21][22][23][24] It is well known that Tregs play a critical role in regulating immune homeostasis, including several pathological conditions such as allergic lung inflammation, autoimmune diseases, transplant rejection and tolerance. [17][18][19][20][21][22][23][24] It is well known that Tregs play a critical role in regulating immune homeostasis, including several pathological conditions such as allergic lung inflammation, autoimmune diseases, transplant rejection and tolerance.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[17][18][19][20][21][22][23][24] It is well known that Tregs play a critical role in regulating immune homeostasis, including several pathological conditions such as allergic lung inflammation, autoimmune diseases, transplant rejection and tolerance. [17][18][19][20][21][22][23][24] It is well known that Tregs play a critical role in regulating immune homeostasis, including several pathological conditions such as allergic lung inflammation, autoimmune diseases, transplant rejection and tolerance.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work revealed that LPS could activate CD4 + CD25 + Tregs via TLR4 signalling. [19][20][21][22] Sepsis is typically characterized by initial hyper-inflammatory Th1 response, which is associated with disease severity and mortality. As we known, Tregs use different pathways to limit inflammatory and immune responses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Restoring macrophage function with cytokines such as interferon (IFN)-β improved survival [17]. Furthermore, the functional decline of peritoneal macrophages occurred within 24 h after the onset of peritonitis and was restored by the systemic administration of IFN-β [18]. Therefore, some septic patients may benefit from early immune-enhancing therapy.…”
mentioning
confidence: 99%
“…For patients undergoing surgery, given that the high surgical insult may lead to the situation similar to infection-induced sepsis, it is thought that early immune-enhancement may also be effective. However, our mouse model showed that the prophylactic administration of IFN-β had a worse outcome for peritoneal sepsis [18].…”
mentioning
confidence: 99%